The Digital Engagement: An Approach to Design the Ecology of Post-Digital Performances - Monda, Letizia Gioia (Mimesis Journal, 2024)
In 2023 Digital Research in Humanities and Arts (DRHA), one of the subjects explored critically and under several perspectives was digital engagement, thus many scholars questioned how digital technologies can trigger the development of innovative strategies designed to socially and culturally empower the audience experience. Those investigations faced a broader range of practices in which digital engagement was assumed as a purpose for activating creative processes to promote tangible and intangible cultural heritage.